2015
DOI: 10.1016/j.talanta.2015.04.083
|View full text |Cite
|
Sign up to set email alerts
|

Integrated, DC voltage-driven nucleic acid diagnostic platform for real sample analysis: Detection of oral cancer

Abstract: We present an integrated and low-cost microfluidic platform capable of extraction of nucleic acids from real biological samples. We demonstrate the application of this platform in pathogen detection and cancer screening. The integrated platform consists of three units including a pretreatment unit for separation of nucleic acids from lysates, a preconcentration unit for concentration of isolated nucleic acids and a sensing unit localized at a designated position on the chip for specific detection of the target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…The AEM is embedded in a circular polyurethane resin pellet and fabricated using a specific molding protocol. 25 A PMMA tubing glued to the resin pellet serves as the “G” terminal reservoir. The reservoirs for the three electrical terminals “D”, “S” and “B” are cut pipette tips and are separated from the channels by filter papers and a layer of 1% agarose gel to prevent possible bubble entry into the channels.…”
Section: Resultsmentioning
confidence: 99%
“…The AEM is embedded in a circular polyurethane resin pellet and fabricated using a specific molding protocol. 25 A PMMA tubing glued to the resin pellet serves as the “G” terminal reservoir. The reservoirs for the three electrical terminals “D”, “S” and “B” are cut pipette tips and are separated from the channels by filter papers and a layer of 1% agarose gel to prevent possible bubble entry into the channels.…”
Section: Resultsmentioning
confidence: 99%
“…As a proof of concept, different biological samples were analyzed in MERCA system. Another integrated microfluidic technology was based on an ionic membrane modular biochip platform developed by Slouka et al, 2015 [124] (Figure 5C). With this modern technique, it is possible to rapidly measure (30-60 min) a maximum of three different miRNAs, stating an LOD of 106 copies with high selectivity and sensitivity, using raw cell media or cell lysate as the substrate.…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…The final target extraction is carried out by a probe-functioned membrane that enhances selectivity and allows the effective quantification of the target probe. [124].…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…In contrast, Slouka et al and Senapati et al developed a simple, single-channel integrated diagnostic platform as shown in Figure 2 , consisting of a pretreatment unit for extraction of nucleic acid biomarkers, a preconcentration unit to concentrate the extracted nucleic acids (reduces assay time by minimizing diffusion limitation) and a nanomembrane-based biosensing unit for selective detection of target nucleic acids [ 195 , 196 ]. The team utilized the inherent charge of nucleic acid molecules and ion-exchange membranes to develop an integrated multiplexed diagnostics platform capable of processing real biological samples and detecting pathogens in 45 min, often without PCR amplification for overexpressed miR targets [ 196 ]. While further validation of this platform using biological and clinical samples is ongoing, the unique features of this system are highlighted below.…”
Section: Recent Developments In Integrated Lab-on-a-chip Technologmentioning
confidence: 99%